UPAYA MENINGKATKAN KEMAMPUAN MENGENAL HURUF MELALUI SAL BERBASIS TEKNOLOGI PADA KELOMPOK A DI TAMAN KANAK-KANAK INDRIASANA KECAMATAN PADANG JAYA BENGKULU UTARA - Soraya Ariyanti; Vivi Anggraini; Nur Hazizah; Mutia Afnida (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
In Group A at Indriasana Kindergarten in Padang Jaya Subdistrict, North Bengkulu Regency, a technology-based Student Active Learning (SAL) method was used to improve early childhood literacy skills. Factors affecting the children’s learning outcomes included their limited ability to recognize letters, lack of focus during the learning process, and low interest in learning. A Classroom Action Research (CAR) study, employing a qualitative approach, was conducted over a two-month period. Children in Group A struggled to identify letters. To collect data, structured observations of the children’s activities and development during the learning process were used. Planning, implementation of actions, observation, and reflection were part of the two research cycles. To implement the SAL method, children were actively engaged in various interactive activities. This included participating in group discussions and using engaging and enjoyable technology-based learning media. The research results showed that the ability to recognize letters had significantly improved. The SAL method not only enhances children’s letter recognition skills but also increases their active participation and self-confidence in learning activities. This method can also serve as an alternative for creative, active, and enjoyable learning approaches in early childhood education settings.